2022
DOI: 10.3389/fpubh.2022.915786
|View full text |Cite
|
Sign up to set email alerts
|

Association between gestational depression and weight management behaviors during pregnancy: A cross-sectional study in Eastern China

Abstract: An undesirable psychological state may deteriorate individual's weight management-related behaviors. This study aims to see if ineffective weight control measures were linked to depressive symptoms during pregnancy. We conducted a cross-sectional questionnaire survey of 784 pregnant women and collected information on sociodemographic factors, maternal characteristics, depression, and weight management activities throughout pregnancy (exercise management, dietary management, self-monitoring regulation, and mana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 36 publications
0
3
1
Order By: Relevance
“…The pandemic situation during the study period and the specific measures taken to contain the virus and mitigate its economic and social impact may also have contributed to the differences observed in the incidence of depression ( 38 ). The incidence of maternal depressive symptoms during late pregnancy in the current study was also much higher than that observed in the general Chinese population (2.1%) ( 18 ). The results of the current study indicate that women in the late pregnancy stage exhibit a higher risk of depression and that the early identification of depression symptoms and appropriate mental health interventions are urgently warranted to protect the mental health of these women.…”
Section: Discussioncontrasting
confidence: 64%
See 2 more Smart Citations
“…The pandemic situation during the study period and the specific measures taken to contain the virus and mitigate its economic and social impact may also have contributed to the differences observed in the incidence of depression ( 38 ). The incidence of maternal depressive symptoms during late pregnancy in the current study was also much higher than that observed in the general Chinese population (2.1%) ( 18 ). The results of the current study indicate that women in the late pregnancy stage exhibit a higher risk of depression and that the early identification of depression symptoms and appropriate mental health interventions are urgently warranted to protect the mental health of these women.…”
Section: Discussioncontrasting
confidence: 64%
“…Concomitantly, health-related education should also be provided to family members ( 39 ). Greater social support for pregnant women may be a viable way to reduce depressive symptoms in this population ( 18 ). This study found that poor social support was associated with maternal depressive symptoms in late pregnancy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Maternal psychological health, which refers to a woman’s mental and emotional well-being during pregnancy, has been found to play a crucial role in GWG through epigenetic changes [ 13 ]. Increased levels of stress, anxiety, and depression during pregnancy have been linked to unfavorable GWG and positive psychological health has been linked with healthier GWG [ 14 ]. The mechanism related to this was found to be interplayed with maternal sleep quality and dietary choices.…”
Section: Introductionmentioning
confidence: 99%